The social impact of a WTO agreement in Indonesia - Robilliard, Anne-Sophie (Policy research working paper, 2005)
"Indonesia experienced rapid growth and the expansion of the formal financial sector during the last quarter of the 20th century. Although this tendency was reversed by the shock of the financial crisis that spread throughout Asia in 1997 and 1998, macroeconomic stability has since then been restored, and poverty has been reduced to pre-crisis levels. Poverty reduction remains nevertheless a critical challenge for Indonesia with over 110 million people (53 percent of the population) living on less than